Building sustainable portfolio careers in music: insights and implications for higher education. (27th May 2019) - Bartleet, Brydie-Leigh; Ballico, Christina; Bennett, Dawn; Bridgstock, Ruth; Draper, Paul; Tomlinson, Vanessa; Harrison, Scott
ABSTRACT: This article discusses a range of significant issues for consideration by music higher education institutions when preparing their students for a portfolio career in music. Drawing on insights from a review of literature undertaken as part of an Australian Research Council Linkage Project, Making Music Work: Sustainable portfolio careers for Australian musicians, the article explores the dynamic structure of the music sector and the ways in which musicians are undertaking a portfolio of roles in order to ensure financial and creative sustainability. In particular, the article focuses on five career and educational issues of importance: enterprise and entrepreneurship, mobility, digitisation, gender parity, and health and wellbeing – when preparing graduates for a portfolio career reality.